A metal-trap tests and refines blueprints to engineer cellular protein metalation with different elements - Sophie E. Clough; Tessa R. Young; Emma Tarrant; Andrew J. P. Scott; Peter T. Chivers; Arthur Glasfeld; Nigel J. Robinson (Nature Communications)
Abstract It has been challenging to test how proteins acquire specific metals in cells. The speciation of metalation is thought to depend on the preferences of proteins for different metals competing at intracellular metal-availabilities. This implies mis-metalation may occur if proteins become mis-matched to metal-availabilities in heterologous cells. Here we use a cyanobacterial MnII-cupin (MncA) as a metal trap, to test predictions of metalation. By re-folding MncA in buffered competing metals, metal-preferences are determined. Relating metal-preferences to metal-availabilities estimated using cellular metal sensors, predicts mis-metalation of MncA with FeII in E. coli. After expression in E. coli, predominantly FeII-bound MncA is isolated experimentally. It is predicted that in metal-supplemented viable cells metal-MncA speciation should switch. MnII-, CoII-, or NiII-MncA are recovered from the respective metal-supplemented cells. Differences between observed and predicted metal-MncA speciation are used to refine estimated metal availabilities. Values are provided as blueprints to guide engineering biological protein metalation.